The negative impact of vitamin D on antipsychotic drug exposure may counteract its potential benefits in schizophrenia. Issue 7 (14th February 2022) - Gaebler, Arnim Johannes; Finner‐Prével, Michelle; Lammertz, Sarah; Schaffrath, Sabrina; Eisner, Patrick; Stöhr, Felix; Röcher, Erik; Winkler, Lina; Kaleta, Peter; Lenzen, Laura; Augustin, Marc; Hovancakova, Jana; et al.
Abstract : Aims: Patients with schizophrenia frequently show insufficient vitamin D levels, which are associated with somatic comorbidity and may contribute to psychopathology. For many reasons, vitamin D supplementation may be indicated for this patient cohort. However, there is growing evidence for a vitamin D‐mediated increase of drug metabolism by induction of cytochrome P450 (CYP) 3A4. Hence, this study aimed to assess vitamin D's impact on both antipsychotic drug concentrations and psychopathology in a non‐interventional manner. Methods: Totals of 107 serum concentrations of different antipsychotic drugs (amisulpride, aripiprazole, clozapine, olanzapine, quetiapine and risperidone), 80 serum concentrations of vitamin D and psychopathological assessments were obtained from 80 patients with schizophrenia. The impact of Vitamin D on antipsychotic drug concentrations and symptomatology was assessed using a generalized linear model, path and correlation analyses. Results: We observed a negative relationship between vitamin D and dose‐adjusted antipsychotic drug concentrations, which was particularly pronounced for drugs which are predominantly metabolized via CYP3A4 (i.e., aripiprazole and quetiapine). A path analysis suggested a relieving effect of vitamin D on symptomatology which was, however, counteracted by its negative impact on antipsychotic drug levels. Finally, patients with vitamin D levels above the median exhibited a significantly higher proportion of therapeutically insufficient dose‐normalized drug concentrations of aripiprazole and quetiapine. Conclusion: Despite vitamin D's potential benefits on physical and mental health, clinicians should be aware of its negative impact on blood concentrations of antipsychotics metabolized by CYP3A4 in patients with schizophrenia. Therefore, when considering its supplementation, therapeutic drug monitoring should be applied to guide dose adjustment.